The Transit from the How to the Pedagogical Why - Arias Prada, Wolfgang Eiffel (2025)
This essay explores an ontology of being with existential possibilities within the framework of developing a proposal for an ontological pedagogy. At the core of this ontology lies the notion of autonomy. To fully understand it, a dialogue is established between enaction and neurophenomenology (Varela), philosophy of mind (Dennett), and Heidegger’s philosophy, complemented by elements of art and popular culture. This innovative approach shifts the focus of educational sciences toward meaning and purpose, rather than merely instrumental components in any sense of the word. Ultimately, it is students who benefit, while teachers themselves undergo a process of transformation.